2021
DOI: 10.1134/s0012496621060028
|View full text |Cite
|
Sign up to set email alerts
|

New Morphofunctional Criteria for Resistance Profile in Post-Traumatic Stress Disorder Models as Adrenal Dysfunction Trigger

Abstract: For the first time in modeling posttraumatic stress disorder (PTSD), we have described the morphofunctional state of adrenal glands in Wistar rats resistant and sensitive to predator stress (rodent fear of the predator). Despite the evident signs of adrenal dysfunction in both phenotypes, we have discovered the thickening of undifferentiated cell zone and high indices of functional activity of stem cells in resistant animals, suggesting ample adaptation. The most important data demonstrate the direct relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Previously, we reported that chronic PS leads to a decrease in plasma Cort with a concomitant increase in proinflammatory cytokines [ 17 , 43 ]. These imbalances support the development of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that chronic PS leads to a decrease in plasma Cort with a concomitant increase in proinflammatory cytokines [ 17 , 43 ]. These imbalances support the development of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The number of entries into the open and closed arms of the EPM and the time spent in the open and closed arms were recorded. Based on these measurements, the AI was calculated [ 17 ]: AI = 1 − {[(time in open arms/Σ time on maze) + (number of entries into open arms/Σ number of all entries)]/2}. An AI > 0.8 was considered a marker for the presence of high anxiety-like behavior; rats with AI > 0.8 were assigned to the HA group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, chronically induced PTSD in the rodents modified the functions and morphology of adrenal gland [ 10 , 26 , 27 ]. This gland plays a crucial role in response to the various psychophysiological situations to keep homeostatic regulation [ 12 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PTSD induction in rats decreased locomotion and rearing behavior, but increased bouts of grooming and instances of immobility [ 46 ]. Furthermore, evidence from animal and human studies showed the events linked to PTSD modify the neural circuits and neurotransmitter systems of brain regions that are crucial for regulation of the psychosocial behaviors such as cognition and affective behavior [ 4 , 9 , 27 ]. These regions are included the hippocampus, the HPA axis, neural networks of fear responses and cognition as well as the dopamine and serotonin (5-HT) systems [ 9 ].…”
Section: Discussionmentioning
confidence: 99%